Research trends of the socio-environmental conflict for oil exploration (2019)
The objective of the article is to present the research development of socio-environmental conflicts for oil exploration. A descriptive interpretative study was carried out through documentary research with a qualitative approach. Fifty research references were reviewed in various databases. In the results, Latin American countries stand out with the highest research output. The predominant method was the case study. It is concluded that the study of socio-environmental conflicts has been increasing in Latin America and with it, the extension of the studied realities from several perspectives. However, the socio-environmental conflictivity has been little approached from the perspective of the thought of the social groups, aspects such as value systems, information, and knowledge of the communities, have not been widely developed in the investigations.